INTERCULTURAL EDUCATION: STATE OF KNOWLEDGE AND THEORETICAL APPROACHES FOR ITS STUDY IN MEXICO - Zhizhko, Elena; Huerta-Vázquez, Mónica-Adriana; Beltrán, Gali-Aleksandra (Studies in Comparative Education, 2024)
This article presents the results of a historical-pedagogical investigation, which objective was to present the state of knowledge and analyze the theoretical approaches for the study of Mexican intercultural education. The study was carried out using the documentary-bibliographic research method. The authors found that regarding the state of knowledge about the problems of intercultural education at international and national levels, it can be stated that in the eighties of the 20th century, social changes at a global level induced the phenomena of multi and pluriculturality, also requiring the development of teaching methodology based on the precepts of interculturalism; intra and intercultural dialogue; transdisciplinarity and respect for difference-similarity. Several researchers agree that it is necessary to build intercultural didactics from the reinterpretation of the curriculum using the critical perspective. Likewise, the analysis of theoretical approaches for the study of intercultural education leads to defining intercultural didactics as an operational didactic model that pursues intercultural education and teaching of the language/s. On the other hand, research on Mexican intercultural education must provide for the analysis of educational programs that involve, on the one hand, indigenous students and, on the other, migrant students returning from the United States.